Determinan Stabilitas Sistem Keuangan Di Indonesia Melalui Pendekatan Makroekonomi - Fristi Wiku; Fitri Juniwati Ayuningtyas (Tirtayasa Ekonomika, 2021)
The condition of financial stability system during the crisis and after the crisis is a benchmark for the financial system in Indonesia, so efforts are needed to avoid or reduce the risk of financial instability system. This situation had an impact on the transmission of monetary policy which could not run effectively and resulted in huge losses for the cost of crisis recovery in a long time. The data analysis method used was the Error Correction Model (ECM). The results showed that in the short term JUB, BI rate, SBI and IHSG had a significant effect on financial stability system, while inflation had no effect on financial stability system. The estimation of the research model in the long term for inflation variables, JUB/M2, BI rate, SBI and IHSG has a significant influence on financial stability system.